(untitled) (Colombia Medica, 1993)
Credentialing is a logical safeguard for patients, physicians, and hospitaís. Laser courses and preceptorships do not credential physicians, but they give them logical support for their credentialing requests to hospital boards. Not all surgeons are competent enough to perform laser surgery, even after several courses and precepts. it is the duty of the credentialing authority to determine which physicians can perform satisfactorily this type of surgery. It is the credentialing authority’s duty to objectively and fairly decide which of the privileges requested should be granted to a laser surgeon based on the data submitted for analysis.